Curriculum Characteristics of Madrasah Aliyah in East Kalimantan - Nasir, Muhammad (IAIN Samarinda, 2020)
This research is aimed to investigate characteristics of curriculum used by Madrasah Aliyah in Samarinda, East Kalimantan. Specifically, document analysis and interview were used to capture the characteristics of curriculum particularly in terms of its structure and development procedures. This research was done in four different Madrasah Aliyah in Samarinda i.e. Madrasah Aliyah (MAN) 2, Madrasah Aliyah (MA) Darul Ihsan, Madrasah Aliyah (MA) Al-Mujahidin, and Madrasah Aliyah (MA) An-Nur. The findings in this research indicate that all Madrasah Aliyah researched in this study have conducted suitable curriculum implementation which is in accordance with Indonesian Educational National Standards that include four aspects i.e. 1) subject course which is divided into compulsory and elective courses; b) local course which include local course programs and values; c) soft skills which contain enforcement of students’ interest such as in the area of language study, arts, sports, and theology; and d) life skills which comprise scouting program and special skills. In addition, the structure of curriculum of all Madrasah Aliyah in this study already contained the main objective of a proper curriculum including course subject, local course, soft skills, life skills, decent spiritual and social behaviors, and special skills. Finally, the future implication is provided in discussion part of the research.